Peningkatan Kemampuan Siswa dalam Membedakan Bahasa Baku dan Bahasa Tidak Baku Berdasarkan EYD - Putri Permata Assiddiq Harahap; Siti Zahra Siagian; Yuli Indriani Lubis; Yeni Yolanda Simbolon; Ika Febriana (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
The ability to differentiate standard language from non-standard language is an important aspect in learning Indonesian. This research aims to examine the effectiveness of using Enhanced Spelling (EYD) in improving students' ability to differentiate between standard and non-standard language. The method used is a literature study by examining in depth the EYD guidelines published by the Language Development and Development Agency, as well as analyzing scientific journals related to the application of EYD in learning. The results of the study show that the EYD guidelines provide a list of standard and non-standard words arranged alphabetically as well as clear and systematic rules for writing standard language. Several previous studies revealed that intensive use of word lists and rules can increase students' mastery of standard vocabulary and understanding of the differences between standard and non-standard language. However, the obstacle in implementing EYD in the field is the teacher's lack of understanding of the existing rules. Therefore, intensive training and socialization is needed for teachers so that the use of EYD can be optimal in improving students' ability to differentiate between standard and non-standard languages. This research concludes that the EYD guide is a very effective source for improving these abilities by providing a clear list of words and standard language rules as a guide for teachers and students.